Fast association rates suggest a conformational change in the MHC class I molecule H-2Db upon peptide binding. - Springer, S; Doring, K; Skipper, J; Townsend, A; Cerundolo, V (1998)
Major histocompatibility complex (MHC) class I molecules bind peptides in the endoplasmic reticulum (ER). For this binding reaction, when performed in vitro, widely differing association rates have been reported. We have expressed empty soluble H-2Db class I molecules in Chinese hamster ovary (CHO) cells and generated complete sets of association, dissociation, and equilibrium constants of unmodified peptides using tritium-labeled peptides and stopped-flow fluorescence spectroscopy. We find that (i) the transition midpoint of temperature denaturation (Tm) of the protein is shifted from 30.5 to 56 degrees C upon the binding of a high-affinity peptide. (ii) With the peptide SV-324-332 (sequence FAPGNYPAL) at 4 degrees C, the dissociation rate constant of 1.02 x 10(-5) s-1 and an equilibrium constant of 8.5 x 10(7) M-1 predict an association rate constant of 870 M-1 s-1 for a simple one-step model of binding. (iii) In contrast, binding of this peptide proceeds much faster, with 1.4 x 10(6) M-1 s-1. These "mismatch kinetics" suggest that peptide binding occurs in several steps, most likely via a conformational rearrangement of the peptide binding groove. The structure of the peptide-class I complex at the time-point of peptide recognition may therefore be different from the equilibrium crystal structures. (iv) Association of modified peptides, in the presence of detergent, or above the Tm of the empty molecule is considerably slower. This might explain why fast on-rates have not been observed in previous studies.